Analisa Occupational Commitment pada Perawat Sarana di Balaiyasa Yogyakarta - damayanti, ajeng tyas; Priyanto, Sapto; handoko, handoko (Jurnal Perkeretaapian Indonesia (Indonesian Railway Journal), 2020)
This research was conducted with the aim to seee the occupational commitment of facility maintainer at Balaiyasa Yogyakarta. The method used in this study uses data collection tools such as questionnaires and interviews. Based on data retrieval that has been done, it is known that as many as 85% of respondents have a high occupational commitment. The recommendation given to the facility maintainer at Balaiyasa Yogyakarta is to develop training that has been done. Some training that can be carried out based on the categorization of occupational commitment includes skills training, retraining, cross-sectional training, team training, information systems training and soft skills training.